2019
DOI: 10.1039/c9qo00206e
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox/rhodium catalysis in C–H activation for the synthesis of nitrogen containing heterocycles

Abstract: The cyclization of acetanilides with alkyne derivatives has been accomplished via a rhodium catalyzed direct C–H functionalization/cyclization pathway in the presence of a photoredox catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 68 publications
0
23
0
3
Order By: Relevance
“…Among recent examples, we highlight the method developed by Wu and co‐workers, which consists of a visible‐light promoted intramolecular cyclization of N ‐aryl‐enaminones employing dual Ir/Co catalysis (Scheme 3a) [27] . Later, Rueping and co‐workers reported a Ru/Rh dual photocatalytic intermolecular approach for the synthesis of indoles from simple anilines and alkynes (Scheme 3b) [28] . As a very important early contribution, Stephenson and co‐workers reported a visible‐light photoredox‐mediated radical reductive deiodination strategy applicable to alkyl, alkenyl, and aryl iodides.…”
Section: Recent Developments On the Photocatalytic Synthesis Of Indoles Oxindoles And Indolinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among recent examples, we highlight the method developed by Wu and co‐workers, which consists of a visible‐light promoted intramolecular cyclization of N ‐aryl‐enaminones employing dual Ir/Co catalysis (Scheme 3a) [27] . Later, Rueping and co‐workers reported a Ru/Rh dual photocatalytic intermolecular approach for the synthesis of indoles from simple anilines and alkynes (Scheme 3b) [28] . As a very important early contribution, Stephenson and co‐workers reported a visible‐light photoredox‐mediated radical reductive deiodination strategy applicable to alkyl, alkenyl, and aryl iodides.…”
Section: Recent Developments On the Photocatalytic Synthesis Of Indoles Oxindoles And Indolinesmentioning
confidence: 99%
“…[27] Later, Rueping and coworkers reported a Ru/Rh dual photocatalytic intermolecular approach for the synthesis of indoles from simple anilines and alkynes (Scheme 3b). [28] As a very important early contribution, Stephenson and co-workers reported a visible-light photoredox-mediated radical reductive deiodination strategy applicable to alkyl, alkenyl, and aryl iodides. As part of the scope investigation, the authors showed that this protocol was also capable of promoting the reductive intramolecular radical cyclization of N-propargyl and N-allyl-2-iodo-sulfonamides affording N-tosyl indoles and indolines in good yields (Scheme 4a).…”
Section: Recent Developments On the Photocatalytic Synthesis Of Indoles Oxindoles And Indolinesmentioning
confidence: 99%
“…In addition, a complementary strategy towards photocatalytic C-H annulation was disclosed by Rueping et al, allowing the synthesis of N-heterocycles such as indoles and pyrroles. The targeted heterocyclic products were obtained by cyclization of acetanilides with alkyne derivatives via a direct ortho-metalation pathway ( Figure 17) [79]. Acetyl substituents acted as DG in this transformation performed under air at high temperatures.…”
Section: Review Visible-light-mediated Photocatalysis As a Sustainablmentioning
confidence: 99%
“…The targeted heterocyclic products were obtained by cyclization of acetanilides with alkyne derivatives via a direct ortho -metalation pathway ( Fig. 17 ) [ 79 ]. Acetyl substituents acted as DG in this transformation performed under air at high temperatures.…”
Section: Reviewmentioning
confidence: 99%
“…(Scheme 25). [44] This strategy shows good functional group tolerance and environmentally friendly. Initially, the neutral dimeric Rh catalyst is converted into its cationic monomeric 67 upon treatment with the silver salt, providing the five‐membered metallacycle 68 via coordination with the oxygen of the acetyl directing group.…”
Section: Photo‐catalyzed/promoted Synthesis Of Indole Derivativesmentioning
confidence: 99%